2021
DOI: 10.4187/respcare.08510
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Transcutaneous Monitoring and Arterial Blood Gases During COPD Exacerbation

Abstract: BACKGROUND: Transcutaneous measurements of CO 2 and O 2 (P tcCO 2 , P tcO 2 ) are noninvasive and allow for continuous monitoring in adults with exacerbation of COPD, but substantial accuracy issues may exist. We investigated agreement between results of arterial blood gas analysis and transcutaneous measurements of CO 2 and O 2 in patients with COPD. METHODS: Adult subjects were monitored after acute admission to a respiratory intermediate care unit or ICU due to exacerbation of COPD and with ongoing noninvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This finding is consistent with studies that have looked at COPD exacerbation cases and found an elevated mean of PaCO 2 of 59 mmHg [ 16 ]. Another recent study looked at COPD cases admitted to ICU with respiratory failure and found the mean PaCO 2 and PaO 2 to be 54 mmHg and 63 mmHg, respectively [ 17 ]. This is in contrast with another study that showed that most patients with COPD do not have elevated PaCO 2 , whereas PaO 2 levels vary between 60 and 80 mmHg [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with studies that have looked at COPD exacerbation cases and found an elevated mean of PaCO 2 of 59 mmHg [ 16 ]. Another recent study looked at COPD cases admitted to ICU with respiratory failure and found the mean PaCO 2 and PaO 2 to be 54 mmHg and 63 mmHg, respectively [ 17 ]. This is in contrast with another study that showed that most patients with COPD do not have elevated PaCO 2 , whereas PaO 2 levels vary between 60 and 80 mmHg [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial blood gas (ABG) analysis is a commonly used tool for monitoring patients with COPD 7 . It provides clinicians with information on the patient's acid–base balance, partial pressures of oxygen and carbon dioxide, as well as levels of hemoglobin, potassium, sodium, and glucose simultaneously.…”
Section: Introductionmentioning
confidence: 99%